Pengembangan Keterampilan Sosial Anak Berhadapan Dengan Hukum (ABH) Pada Program Vokasional Di Sentra Handayani - Mia Nursapitri; Muhammad Sahrul (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
In recent years, Indonesia has seen an increase in child rights violations, specifically cases of Children Against the Law (ABH). The Indonesian Child Protection Commission (KPAI) recorded 29,322 cases of complaints related to violations of children's rights from 2017-2022, including cases involving children dealing with the law. This research aims to assess the effectiveness of the vocational program conducted by Sentra Handayani in developing the social skills of ABH. The research is a descriptive qualitative study, where the researcher directly observes and records phenomena without manipulating variables. Sentra Handayani offers various rehabilitation programs, including a vocational program. The study applies the social skills theory of Gresham & Elliot (2008), which identifies cooperation, assertiveness, responsibility, empathy, and self-control as key aspects of social skills. The results indicate that three aspects, namely cooperation, responsibility, and self-control, require reaffirmation and supervision as there were no significant changes. However, the aspects of assertiveness and empathy showed positive developments.